Comparative Study on the Structures of Chinese and Korean Compound Words - Xun, Zhai; Hee, Yoo Eun (Lingua Cultura, 2016)
The goal of the research was to compare the compound words in Chinese, an isolated language, and Korean, an agglutinative language. This research used library research. The researchers found that the main characteristics of the formation of Korean compound words were that the latter element was the central word. The method of word formation decided its lexical category. Moreover, most of the internal relationships of the compound words were connection and modification. While in Chinese, the endocentric compound noun decided the part of speech of the compound word, and could be the proceeding element or the latter element. Furthermore, Chinese contained no complicated morphological changes. It is concluded that Korean is a Subject–Object–Verb (SOV) language, where verb elements demonstrate a central feature of the compound verb are always a trailing part. Thus, there is no exocentric compound verb in Korean. By contrast, Chinese is a typical SVO language. When constituting the compound verbs, nouns or adjectives can function as the structural elements. Therefore, there is no permanent position for head words.